1970
DOI: 10.1083/jcb.46.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical and Developmental Changes in Microbodies (Glyoxysomes) and Related Organelles of Castor Bean Endosperm

Abstract: Structural changes in endosperm cells of germinating castor beans were examined and complemented with a cytochemical analysis of staining with diaminobenzidine (DAB) . Deposition of oxidized DAB occurred only in microbodies due to the presence of catalase, and in cell walls associated with peroxidase activity . Seedling development paralleled the disappearance of spherosomes (lipid bodies) and matrix of aleurone grains in endosperm cells . 6 to 7 days after germination, a cross-section through the endosperm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
1
5

Year Published

1973
1973
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(121 citation statements)
references
References 46 publications
(73 reference statements)
6
109
1
5
Order By: Relevance
“…The elongated vesicular nature of the membranes and dense association of ribosomes is quite similar to that seen in the electron micrographs prepared from intact endosperm tissue (29,42) .…”
Section: Effect Of Mg++ On Sedimentation Behaviorsupporting
confidence: 61%
See 2 more Smart Citations
“…The elongated vesicular nature of the membranes and dense association of ribosomes is quite similar to that seen in the electron micrographs prepared from intact endosperm tissue (29,42) .…”
Section: Effect Of Mg++ On Sedimentation Behaviorsupporting
confidence: 61%
“…The fact that inclusion of Mg++ in the gradients yielded enzymatically active fractions of higher density comprised of rough endoplasmic reticulum, and the prevalence of similar structures in sections of living cells (29,42) strongly suggest that this is the location of the enzyme in vivo. Membranes of mitochondria and glyoxysomes from castor bean endosperm contain lecithin as a major structural phospholipid (23,25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether pexophagy occurs in plant cells is not clear (Hu et al, 2012), despite evidence supporting it. First, electron microscopic observation suggested pexophagy in castor bean (Ricinus communis) endosperm (Vigil, 1970), although similar observations have not been reported. Second, Atg genes encoding core autophagic machineries are highly conserved in various eukaryotes, including dicots (Hanaoka et al, 2002;Doelling et al, 2002) and monocots (Chung et al, 2009), and reverse genetic studies using Arabidopsis demonstrated their functions in plant autophagy (reviewed by Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Less is known, however, about the aleurone pcd pathway. Cell death in aleurone and endosperm cells during germination of seeds appears to involve autophagic vacuoles (Vigil, 1970;Reid and Meier, 1972), and, in wheat aleurone, is preceded by an increase in cytosolic calcium levels (Kuo et al, 1996). It was also recently discovered that death of wheat aleurone cells is prevented by treatment with okadaic acid and hence appears to depend on protein phosphatase activity (Kuo et al, 1996).…”
Section: Aleurone Deathmentioning
confidence: 99%